AKUARIUM BIOTA LAUT DENGAN PENDEKATAN ARSITEKTUR METAFORA DI TAMAN NASIONAL KARIMUN JAWA - Meikalista, Adelia; Musyawaroh, Musyawaroh; Hardiana, Ana (Universitas Sebelas Maret Surakarta, 2016)
Indonesia is an archipelago that 63% of the territory is water area and has a fascinating natural beauty one of which is underwater paradise, one of them is Karimunjawa Islands. Karimunjawa National Park is famous for it’s underwater paradise, so that few people who visit it’s main purpose is closely bound with snorkeling and diving activities. But from year to year in the state of degradation of marine life, so that need a place for conservation and research for the marine life. Marine aquarium is an alternative that can be used as a place for introduction of underwater life, and can become a place of preservation and research on marine life. Design problems in designing marine aquarium is how marine aquarium into the separate icon for Karimunjawa National Park which portray the richness of marine life there, so to make that image then approach the Architecture Metaphor is very suitable as a concept design planning aquarium marine life. Metaphor architecture can be applied to the design of marine aquarium by adopting the coral reefs are applied to the regulatiuon of site, the space in the mass, the shape and composition of it’s mass. This concept of life in the ocean can be visualized with the architectural design as well as being of architectural presenting function. Keywords: Aquarium, Conservation, Marine, Marine Aquarium, Marine Biota, Marine Life, Metaphor Architecture, Research.